THE CORRELATION OF PARENTS' COMMUNICATION ABILITY TO THE SOCIAL EMOTIONAL DEVELOPMENT OF SCHOOL AGE CHILDREN 6-8 YEARS IN KERTASARI VILLAGE IN 2022 - Amelia, Sindi; Hilda Meriyandah Agil; Nurti Yunika K. Gea (Rena Cipta Mandiri, 2025)
The pattern of communication that is applied in the family, especially the attitude of parents in educating and caring for their children is very influential on the emotional development of children. In this case, parents become values ​​for children. The values ​​instilled by parents will be more digested and adopted by children. The first treatment of parents, will be recorded by the child and affect emotional development and will gradually shape his personality. Research Objectives: This study aims to determine the relationship of parental communication skills to the social emotional development of school age children 6-8 years in paperari village in 2022. Research Methods: The research method used is quantitative with cross-sectional analytic research. The population in this study was the community of Kertasari Village in 2022 totaling 114 respondents. Data collection techniques using purposive sampling type. The results of the study: It was found that there was a significant level of 95% or a value of 5% (0.05). Chi Square test results obtained p value of (0.000) < value of (0.05). There is a Relationship between Parental Communication on Social Emotional Development of School Age Children 6-8 Years Old in Kertasari Village in 2022. Conclusion: There is a Relationship between Parental Communication on Social Emotional Development of School Age Children 6-8 Years Old in Kertasari Village in 2022.